Development Strategy and Governance Division (DSGD) - International Food Policy Research Institute (International Food Policy Research Institute, 2018)
The Sustainable Development Goals of the United Nations focus on many of the aims central to IFPRI’s mandate, including tackling poverty, hunger, and malnutrition. Achieving such goals requires multifaceted development strategies that generate inclusive economic growth for men, women, and youth in both urban and rural areas. Designing cost-effective strategies requires micro- and macro-analyses that take into account many of the emerging issues facing the developing world, including an increasingly competitive global environment for agricultural trade, the rapid expansion of cities and secondary towns, persistent high underemployment and, in many countries, protracted political transitions. In recognition of these challenges, IFPRI’s Development Strategy and Governance Division (DSGD) engages in rigorous, policy-relevant research, outreach, and capacity strengthening to promote sustainable and socially inclusive rural development. This work contributes to two of the five research areas in IFPRI’s 2018–2020 Strategy: (1) transforming agricultural and rural economies and (2) strengthening institutions and governance.